Zinc Supplementation in Treatment of Children With Urinary Tract Infection (Iranian Journal of Kidney Diseases, 2016)
Introduction. Urinary tract infection (UTI) is very common in children. Precocious diagnosis and appropriate treatment are important because of the permanent disease complications. Zinc increases the response to treatment in many infections. In this study, we explored the effect of zinc in treating UTI. Materials and Methods. Two hundred children with UTI were divided into 2 groups of 100 who were comparable in terms of age, sex, urine laboratory profiles, and clinical signs and symptoms. The control group received a standard treatment protocol for UTI and the intervention group received oral zinc sulfate syrup plus routine treatment of UTI. Results. A faster recovery was observed in the patients receiving zinc, but abdominal pain was exacerbated by zinc and lasted longer. Three months after the treatment, there was no significant difference between the two groups in the time of fever stop and negative urine culture. Conclusions. In children with UTI, zinc supplementation has a positive effect in ameliorating severe dysuria and urinary frequency while the use of this medication is not recommended in the presence of abdominal pain.